EXPLORATORY DATA ANALYSIS HISTORI LAGU YANG DIDENGARKAN DI SPOTIFY TAHUN 2020-2021 - Orlen Bahtiar Khan, (2023)
Spotify is a streaming service application that is one of the most popular in the streaming platform segment. As of the first quarter of 2021, Spotify's monthly active listeners have touched the 356 million mark. Researchers see the potential of Spotify where the data will be presented visually. Using a graphical bivariate method and Python for data processing, this study aims to find out who are the popular artists and genres based on data visualization showing the most popular artists in 2020 and 2021, as well as what are the favorite genres in one of the playlists. A total of 2,703,876 data records for history and 54 songs in playlists are needed to carry out this research which will run for approximately 5 months. The results of this study are in the form of three bar charts each showing the top 20 artists in 2020, 2021 and 2020-2021 from users' streaming history data, as well as one chart containing the 20 most popular genres in a playlist.